2020
DOI: 10.1186/s12891-020-3065-3
|View full text |Cite
|
Sign up to set email alerts
|

Which anatomic structures are responsible for the reduction loss after hybrid stabilization of osteoporotic fractures of the thoracolumbar spine?

Abstract: Introduction: Hybrid stabilization is an accepted therapy strategy for unstable osteoporotic thoracolumbar fractures. However, a moderate reduction loss has been reported and it remains unclear which anatomic structure is responsible for the reduction loss. Methods: This retrospective study was performed at a level I trauma center. Patients aged 61 and older were stabilized using hybrid stabilization after suffering acute and unstable osteoporotic vertebral body fractures at the thoracolumbar spine. Posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Different strategies of hybrid stabilization about the combination of cement augmentation accompanied with posterior instrumentation for the treatment for unstable osteoporotic burst fractures have been reported, most of the studies demonstrated satisfactory clinical and radiological results, however, loss of reduction was unavoidable, the rang can be high to 4.6° to 23°, the causes of reduction appear to be the structural and mechanical deficiency of the anterior-middle columns [ 20 , 21 ]. Recent study reported that the superior disc adjacent to the fractured vertebral body and the central part of the fractured vertebral body seem to be responsible for the majority of reduction loss, and this might be reduced by optimal cement technique and cement positioning between the upper and middle third of center and the anterior third of the fractured vertebral body [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies of hybrid stabilization about the combination of cement augmentation accompanied with posterior instrumentation for the treatment for unstable osteoporotic burst fractures have been reported, most of the studies demonstrated satisfactory clinical and radiological results, however, loss of reduction was unavoidable, the rang can be high to 4.6° to 23°, the causes of reduction appear to be the structural and mechanical deficiency of the anterior-middle columns [ 20 , 21 ]. Recent study reported that the superior disc adjacent to the fractured vertebral body and the central part of the fractured vertebral body seem to be responsible for the majority of reduction loss, and this might be reduced by optimal cement technique and cement positioning between the upper and middle third of center and the anterior third of the fractured vertebral body [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors found a significantly better vertebral body height restoration, significantly lower Cobb angles, and a reduced number of adjacent fractures after additional posterior stabilization compared to kyphoplasty of the fractured vertebral body alone. Spiegl et al [ 28 ] analyzed the structures which are responsible for the reduction loss after hybrid stabilization at the thoracolumbar junction and found the highest loss at the intervertebral disc adjacent to the fracture. Thus, the beneficial effect of a persistent restoration of the vertebral height on the sagittal alignment might be even more pronounced in the midthoracic spine based on the smaller intervertebral discs.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional SSPF system replaces the fractured vertebral body by indirect traction. The fractured vertebral body can be effectively reduced by the traction of the fibrous annulus of the intervertebral disc, but the central bone mass of the anterior and middle column cannot be pulled, resulting in a central collapse defect, resulting in insufficient reduction [26,27]. Although the height and shape of the fractured vertebral BioMed Research International body are restored after indirect reduction, it is difficult to restore the trabecular structure in the vertebral body.…”
Section: Discussionmentioning
confidence: 99%